Cytotoxicity of Copper Ions Released from Metal : Variation with the Exposure Period and Concentration Gradients - Cortizo, María Cecilia (2004)
The aim of this work is to contribute to the elucidation of the cytotoxic process caused by the copper ions released from the biomaterials. Clonal cell lines UMR106 were used in the experiments. Copper ions were obtained from two different sources: copper salts and metal dissolution. Experiments carried out with constant ion concentrations (copper salts) were compared with those with concentrations that vary with time and location (dissolution of the metal). Present results and others previously reported could be interpreted through mathematical models that describe: (1) the variation of concentration of copper ions with time and location within a biofilm and (2) the variation of the killing rate with the concentration of the toxic ion and time. The large number of dead cells found near the copper sample with an average ion concentration below the toxic limit could be interpreted bearing in mind that these cells should be exposed to a local concentration higher than this limit. A logarithmic dependence between the number of cells and exposure time was found for nearly constant ion concentrations. Apparent discrepancies, observed when these results and those of different researchers were contrasted, could be explained considering the dissimilar experimental conditions such as the source of the ions and their local concentration at real time.